A preliminary annotated bibliography of materials on Indonesia written and/or published in the Philippines, 1936-1982 - Laoccong, Mustafa (1983)
There are many materials about Indonesia written or published in the Philippines. These can be found in many libraries in the form of books, pamphlets, periodical and newspaper articles as well as theses and dissertations.